2018
DOI: 10.1007/s00246-018-1813-z
|View full text |Cite
|
Sign up to set email alerts
|

Flow Energy Loss as a Predictive Parameter for Right Ventricular Deterioration Caused by Pulmonary Regurgitation After Tetralogy of Fallot Repair

Abstract: The optimal timing for pulmonary valve replacement after Tetralogy of Fallot (TOF) repair remains controversial. In this study, we estimated the feasibility of using flow energy loss (FEL) to predict right ventricular (RV) deterioration due to pulmonary regurgitation after TOF repair. We examined RV outflow tract (RVOT) flow in nine patients who underwent TOF or double-outlet right ventricle repair in the intervention group (Group I) and compared them with three healthy children in the control group (Group C).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…Secondly, the software is used to applying in intraventricular flow velocity calculation, not atrial. EL reflects the total differences of neighboring velocity vectors; In the light of the principal of VFM (Figure ), the velocity vector component within LA is available and convincible, as the low velocity in LA ensures the quality of 2D color Doppler without the need for very high frame rates; it is reasonable, therefore, in our opinion, that the equation can be extrapolated to other chambers, like, as reported, the atrium or right ventricle …”
Section: Discussionmentioning
confidence: 83%
“…Secondly, the software is used to applying in intraventricular flow velocity calculation, not atrial. EL reflects the total differences of neighboring velocity vectors; In the light of the principal of VFM (Figure ), the velocity vector component within LA is available and convincible, as the low velocity in LA ensures the quality of 2D color Doppler without the need for very high frame rates; it is reasonable, therefore, in our opinion, that the equation can be extrapolated to other chambers, like, as reported, the atrium or right ventricle …”
Section: Discussionmentioning
confidence: 83%
“…Echocardiography VFM enables us to evaluate the cardiac workload. Evaluation of pulmonary valve stenosis and association between right ventricular function deterioration and EL using VFM technology have been reported [3,9]. One of the wellknown concept of EL is the "energy loss concept," which is used to evaluate aortic stenosis [10], and the energy loss index is one of the predictors of prognosis in asymptomatic aortic stenosis [11].…”
Section: Discussionmentioning
confidence: 99%
“…FEL is known as a parameter of cardiac workload to predict ventricular deterioration in various heart diseases [6,7], including heart valve disease, cardiomyopathy, and congenital heart disease. Regarding the right ventricular deterioration, Shibata et al reported that FEL through the pulmonary valve after tetralogy of Fallot (TOF) repair was correlated with QRS duration prolongation in an electrocardiogram [8]. In our case, her FEL of the rightsided heart system calculated from four-dimensional flow MRI was very high due to the combination of It is reported that RV cannot obtain reverse remodeling of the normal range after pulmonary valve replacement (PVR), if re-operation is too late [9].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the right ventricular deterioration, Shibata et al . reported that FEL through the pulmonary valve after tetralogy of Fallot (TOF) repair was correlated with QRS duration prolongation in an electrocardiogram [ 8 ]. In our case, her FEL of the right-sided heart system calculated from four-dimensional flow MRI was very high due to the combination of moderate RVOT stenosis, moderate PR, and severe TR.…”
Section: Discussionmentioning
confidence: 99%